2020
DOI: 10.1021/acsearthspacechem.9b00327
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Asian Dust in Daejeon, Korea, during the Spring Season

Abstract: Number of figures : 1 Number of tables : 3 Table S1. Results of major elemental concentrations (mg•kg-1) as determined by WD-XRF and k0-INAA for cross validation of methods. Results are given with the expanded uncertainty of k = 2 elements YD17 YD18 YD19 WD-XRF k0-INAA % dev. WD-XRF k0-INAA % dev. WD-XRF k0-INAA % dev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Air pollutants such as yellow and fine dust, have become a critical social issue and are life-threatening to patients with respiratory diseases. Several studies [ 1 , 2 , 3 , 4 ] have particularly reported that titanium dioxide nanoparticles (TiO 2 NPs), components of Asian dust and air pollutants, exacerbate respiratory distress [ 1 , 2 , 3 , 4 ]. Moreover, TiO 2 NPs induce an intensive inflammatory response by triggering inflammatory cell migration and pro-inflammatory cytokine secretion, consequently contributing to the development and exacerbation of respiratory diseases [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollutants such as yellow and fine dust, have become a critical social issue and are life-threatening to patients with respiratory diseases. Several studies [ 1 , 2 , 3 , 4 ] have particularly reported that titanium dioxide nanoparticles (TiO 2 NPs), components of Asian dust and air pollutants, exacerbate respiratory distress [ 1 , 2 , 3 , 4 ]. Moreover, TiO 2 NPs induce an intensive inflammatory response by triggering inflammatory cell migration and pro-inflammatory cytokine secretion, consequently contributing to the development and exacerbation of respiratory diseases [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The elemental mass fraction values labeled # in Table 2 represent non-accredited activities, in accordance with LP-090, beyond the scope of the range of testing or the specified uncertainty. All details of uncertainty evaluation of k0-INAA method is explained in our previous studies [13,38] and the literature [32]. The expanded uncertainties for mass fraction values represented in Table 1 and Table 2 have a coverage factor k = 2 at 95% confidence level.…”
Section: Validation Of the K 0 -Inaa Methods Using Nist Srm 1648a Urban Pmmentioning
confidence: 99%
“…However, the contribution of fission of 235 U may be ignored if only a low amount of U is present in the sample, which is not the case of NIST SRM 1648a. All details of uncertainty evaluation of k 0 -INAA method is explained in our previous studies [13,38] and the literature [32]. The expanded uncertainties for mass fraction values represented in Tables 1 and 2 have a coverage factor k = 2 at 95% confidence level.…”
Section: Validation Of the K 0 -Inaa Methods Using Nist Srm 1648a Urban Pmmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollutants, such as yellow dust and ne dust, have become a critical social issue and are lifethreatening to patients with respiratory diseases. In particular, titanium dioxide nanoparticles (TiO 2 NPs), a component of Asian dust and air pollutants, have been reported to exacerbate respiratory distress in several studies [1][2][3][4]. Moreover, TiO 2 NPs induce an intensive in ammatory response by triggering in ammatory cell migration and pro-in ammatory cytokine secretion, and consequently, contributing to the development and exacerbation of respiratory diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%